Aplikasi Pembayaran Iuran Sekolah Katolik Yayasan Sagrado Coração de Jesus Berbasis Web - Henriques, Romeu O.; Manehat, Donatus Joseph; Sinlae, Alfry Aristo Jansen (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
The Sagrado Coração de Jesus Foundation is a formal educational institution that manages 58 Catholic schools in the Maliana Diocese of Timor Leste. In dealing with the payment of fees, Catholic schools under the Sagrado Coração de Jesus Foundation still use books to record payment transactions. These transactions must be carried out at the foundation, and it takes a long time to record transactions in the book so that it becomes a problem faced by the foundation, schools, and parents of students. A web-based school tuition payment application is needed by the Sagrado Coração de Jesus Foundation to handle the school's tuition payment activities on behalf. The use of website media makes it easier for parents to show proof of payment without having to come to the foundation. Applications that are built can also speed up the process of recording the payment of contributions by foundation employees. Based on the research results, the Web-based application for payment of tuition fees for Catholic schools at the Sagrado Coração de Jesus Foundation makes it easier for parents and foundations to make payment transactions more efficiently and quickly.